Manajemen Pengembangan Sumber Daya Anggota (PSDA) KOPMA UIN Sunan Kalijaga Yogyakarta (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2021)
The ups and downs of the journey of KOPMA UIN Sunan Kalijaga Yogyakarta was able to give an idea to all its cadres that the optimization of the development of member resources was not optimal. This study aims to describe how the process and implementation of human resource management in the development of member resources (PSDA) of KOPMA UIN Sunan Kalijaga Yogyakarta. So that it is hoped that in the future the cadres are required to be able to optimize the development of the resources of KOPMA UIN Sunan Kalijaga Yogyakarta members to achieve common goals. The research is a type of qualitative research whit data collection carried out by conucting observations, interviews and documentation. The validity of the data was tested by using triangulation technique. The results showed that:1) human resource management of KOPMA UIN Sunan Kalijaga Yogyakarta through: a) planning and recruitmen: b)selection process: c) education and training; d)career development; e) comensation. 2) development of mamber resourvces (PSDA) of KOPMA UIN Sunan Kalijaga Yogyakarta through: a) member development; b) communication media; c) membership administration; d) member welfare; e) special programs.